2008
DOI: 10.1016/j.ejpain.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of NaV1.7, NaV1.8 and NaV1.9 in a distinct population of dorsal root ganglia innervating the rat knee joint in a model of chronic inflammatory joint pain

Abstract: Voltage-gated sodium channels play an essential role in regulating the excitability of nociceptive primary afferent neurones. In particular the tetrodotoxin-sensitive (TTX-S) Na(V)1.7 and the tetrodotoxin-resistant (TTX-R) Na(V)1.8 and Na(V)1.9 channels have been suggested to play a role in inflammatory pain. Previous work has revealed acute administration of inflammatory mediators, such as Freund's complete adjuvant (FCA) or carrageenan caused an upregulation in the levels of Na(V)1.7 and Na(V)1.8 protein in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 42 publications
4
107
0
2
Order By: Relevance
“…Inflammation in rat hind paws was shown to induce NaV up-regulation in axons of digital nerves [32], and peripheral inflammation following carrageenan injection was reported to increase the expression of NaV1.7 in DRG neurons [33]. In addition, the expression of NaV1.7 in a distinct population of DRG innervating the rat knee joint was increased in a model of chronic inflammatory joint pain [34]. Furthermore, some authors have demonstrated a decrease in inflammatory hyperalgesia in response to herpes vector-mediated knockdown of NaV1.7 in primary afferents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammation in rat hind paws was shown to induce NaV up-regulation in axons of digital nerves [32], and peripheral inflammation following carrageenan injection was reported to increase the expression of NaV1.7 in DRG neurons [33]. In addition, the expression of NaV1.7 in a distinct population of DRG innervating the rat knee joint was increased in a model of chronic inflammatory joint pain [34]. Furthermore, some authors have demonstrated a decrease in inflammatory hyperalgesia in response to herpes vector-mediated knockdown of NaV1.7 in primary afferents.…”
Section: Discussionmentioning
confidence: 97%
“…The current model includes elements of inflammation and compressive nerve injury, as mentioned above. Peripheral inflammation increases the expression of NaV1.7 in peripheral nerves and DRG [32][33][34]. Inflammation in rat hind paws was shown to induce NaV up-regulation in axons of digital nerves [32], and peripheral inflammation following carrageenan injection was reported to increase the expression of NaV1.7 in DRG neurons [33].…”
Section: Discussionmentioning
confidence: 99%
“…Auch die Attackenreduktion bei jedem unserer 5 betroffenen Patienten ist so eventuell erklärbar. Eine gesteigerte Na v 1.8-Expression findet sich ferner bei diabetischer Polyneuropathie [30], Smallfiber-Neuropathie [19], Radikulopathien [17,44], Trigeminusneuralgie [41], aber auch bei Arthrosen [39,43] und Knochenmetastasen [33]. Die Na v 1.8-Blockade, z.…”
Section: Na V 18-expressionunclassified
“…Two isoforms of the α-subunit of VGSCs, Na V 1.7, and Na V 1.8, are expressed at high levels in nociceptive sensory neurons. 8 Multiple lines of evidence show that they have been implicated in the development of inflammatory pain 9,10 and neuropathic pain. [11][12][13] Furthermore, dysregulation of VGSCs in injured sensory neurons is also involved in the development of painful peripheral neuropathy in a rat model of diabetes.…”
Section: Introductionmentioning
confidence: 99%